UNIVERSITY MANAGERS PARTICIPATION IN DISTANCE EDUCATION: THE ROLE OF DISTANCE EDUCATION SUPPORT FACILITIES - Naomi, Gikonyo; Anne, Ndiritu; Guantai, Mboroki (European Scientific Journal, ESJ, 2014)
Universities continue to develop new methods of teaching in order to reach many people who cannot access education through the conventional methods; and to attain equity and increase access in higher education for development. Education is a key pillar in development. As Kenya works towards the attainment of Vision 2030 a lot has to be done in education to increase equity and access to allow many people to participate in the development. A lot of resources have been committed to development and implementation of DE materials and facilities but adoption of DE continues to be minimal at the Kenyan Public universities. This paper explores the role DE support facilities plays in the participation of university managers in DE activities in Kenya’s Public Universities. To study this role, the following indicators were analysed: computer availability to the managers and staff; access to personal computer; internet availability; number of internet connection points; and availability of ICT help desk. The study sort to establish the extent to which availability of personal computers availability of internet, number of internet connection points, availability of computers for teaching influence managers’ participation in DE; and to assess the availability of ICT help desks. The research employed cross-sectional descriptive survey design; and multi-stage stratified sampling design. The findings indicated that availing necessary support facilities is crucial if adoption of DE is to be increased in the public universities in Kenya. This study recommends that the university management avails the necessary support facilities to ensure participation in distance education activities. The management should work towards identifying strategies that can improve managers’ participation at different levels. The study also recommends training to enhance attitude transformation.